2020
DOI: 10.4236/oalib.1105831
|View full text |Cite
|
Sign up to set email alerts
|

Status of Rohingya Refugees in Bangladesh: A Comparative Study with Emphasis on Aspects of Women and Girls in Camps of Kutupalong, Cox’s Bazar, Bangladesh

Abstract: A continuous flow of Rohingya refugees in Bangladesh because of violence in Rakhine State in Myanmar causes consequence to the world's largest refugee camp where most of the refugees are women and children. This study was conducted in 2018 in Bangladesh to understand the comparative status of registered and newly arrived Rohingya people in Kutupalong camps of Cox's Bazar focusing the present conditions of women and girls. This research explores the comparative information of registered and newly arrived Rohing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…The study areas are located in the Kutupalong camp of Ukhia Upazila of Cox's Bazar district in Chittagong, Bangladesh, highlighted in Figure 1 (Section 1.1). Kutupalong is one of the mega-camps, consisting of 22 camps and over 600,000 individuals [52]. After consultation with the Additional Refugee Relief and Repatriation Commissioner (RRRC), refugee Camp 2 East (2E), 2 West (2W), and Camp 4 Extension (4Ext) were chosen for this study.…”
Section: Study Areamentioning
confidence: 99%
“…The study areas are located in the Kutupalong camp of Ukhia Upazila of Cox's Bazar district in Chittagong, Bangladesh, highlighted in Figure 1 (Section 1.1). Kutupalong is one of the mega-camps, consisting of 22 camps and over 600,000 individuals [52]. After consultation with the Additional Refugee Relief and Repatriation Commissioner (RRRC), refugee Camp 2 East (2E), 2 West (2W), and Camp 4 Extension (4Ext) were chosen for this study.…”
Section: Study Areamentioning
confidence: 99%
“…Due to the usage of plastic sheets, tarpaulin, clay, brick and bamboo, they are often vulnerable to coastal disasters. On average, each refugee occupies a space of 9.5 square meters, while the normal dwelling area, according to Sphere, should be 30 square meters under camp conditions, excluding gardens (Karin, Chowdhury, & Shamim, 2020). The survey also found that women were disadvantaged in bathing and toilet services due to a lack of water, hygiene, privacy and male assault (Akhter & Kusakabe, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…UN agencies and NGOs have also established that Rohingya refugees are denied livelihood opportunities and forced to subsist in congested camps in Bangladesh (UNICEF, 2018). However, few studies identified the status of RRs living in Bangladesh and their specific challenges (Karin, Chowdhury, Hasnat, & Tarin, 2020; Karin, Chowdhury, & Shamim, 2020). For example, Khan et al.…”
Section: Introductionmentioning
confidence: 99%
“…The refugees must live in fragile constructed shelters made of bamboo, brick, and mud, where extreme heat and a lack of ventilation make it extremely unsanitary and dangerous to stay. Women face discrimination in terms of bathing and toilet facilities, where many women face a lack of water and privacy issues, as well as violence from men in terms of livelihood conflicts (Karin et al, 2020). The United Nations Population Fund (UNFPA) has assisted 3500 Rohingya women who have been sexually assaulted since late August 2017.…”
Section: Literature Reviewmentioning
confidence: 99%